Influence of supporting teeth quantity of surgical guide on the accuracy of the immediate implant in the maxillary central incisor: an in vitro study - Meo Nguyen; Huynh Kim Khanh Nguyen; Thien Nga Nguyen; Nam Cong-Nhat Huynh (BDJ Open)
Abstract Introduction Guided surgery for immediate anterior implants aims to reduce the time required for aesthetic and functional immediate loading. However, the limited surface area of anterior teeth for guide stabilization may affect the accuracy of implant positioning. This in vitro study evaluated the effect of the number of supporting teeth on the accuracy of immediate implants in the maxillary central incisor region. Methods 28 replica implants were inserted into 28 upper jaw models, simulating immediate post-extraction sockets of tooth 11. Based on the number of supporting teeth, the implants were categorized into G1 (four adjacent teeth) and G2 (six adjacent teeth). The planned and actual implant positions were compared using the evaluation module of the implant planning software. Angular and 3D deviations were measured as the primary outcomes. Statistical analysis was performed using the two-sample t-test, with p-values less than 0.05 defined as statistically significant. Results Between group G1 and G2, angular deviation was measured at 4.63 ± 0.71° and 3.59 ± 0.97°, respectively, while the implant apex 3D deviation was 2.08 ± 0.21 mm for G1 and 1.40 ± 0.27 mm for G2. These differences were statistically significant (p = 0.003 and p < 0.001, respectively). Other discrepancy variables in G2 demonstrated lower values but were not statistically significant compared to G1. Conclusion The number of supporting teeth for the surgical guide can influence the accuracy of immediate implant surgery. While both four-teeth and six-teeth supports demonstrated acceptable clinical implant accuracy, a surgical guide supported by six teeth can enhance implant precision.